PENGARUH LOCUS OF CONTROL DAN SELF-REGULATED LEARNING TERHADAP PROKRASTINASI AKADEMIK PADA PESERTA DIDIK AKUNTANSI DAN KEUANGAN LEMBAGA DI SMK - Gustina Handayani; Sri Sumaryati; Jaryanto Jaryanto (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2023)
Abstract This study aims to examine (1) the effect of locus of control on academic procrastination in Accounting and Financial Institution students at SMK N X (2) the effect of self-regulated learning on academic procrastination in Accounting and Financial Institution students at SMK N X (3) the effect of locus of control and self-regulated learning on academic procrastination in Accounting and Financial Institution students at SMK N X. This study uses a quantitative descriptive method with a correlational approach. The population in this study are all students of the Accounting and Institutional Finance expertise program at SMK N X for the 2022/2023 academic year with a total of 319 students. The sampling technique in this study uses a proportional random sampling technique which obtains 177 samples. Data analysis techniques using descriptive statistical analysis and multiple linear regression analysis. The results of this study are: (1) there is a significant influence between locus of control on academic procrastination of students in Accounting and Financial Institutions at SMK N X; (2) there is a significant influence between self-regulated learning and academic procrastination of students in Accounting and Financial Institutions at SMK N X; (3) there is a significant influence between locus of control and self-regulated learning on academic procrastination of Accounting and Financial Institution students at SMK N X. Keywords: locus of control, self-regulated learning, and academic procrastination Abstrak Penelitian ini bertujuan untuk menguji (1) pengaruh locus of control terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X (2) pengaruh self-regulated learning terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X (3) pengaruh locus of control dan self-regulated learning terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X. Penelitian ini menggunakan metode deskriptif kuantitatif dengan pendekatan korelasional. Populasi dalam penelitian ini adalah seluruh siswa program keahlian Akuntansi dan Keuangan Lembaga di SMK N X tahun ajaran 2022/2023. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik proportional random sampling dan diperoleh sampel sebanyak 177 siswa. Teknik analisis data menggunakan analisis statistik deskriptif dan analisis regresi linear berganda. Hasil dari penelitian ini adalah: (1) terdapat pengaruh signifikan antara locus of control terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X; (2) terdapat pengaruh signifikan antara self regulated learning terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X; (3) terdapat pengaruh signifikan antara locus of control dan self regulated learning terhadap prokrastinasi akademik peserta didik Akuntansi dan Keuangan Lembaga di SMK N X. Kata kunci: locus of control, self regulated learning, dan prokrastinasi akademik